2007
DOI: 10.1111/j.1467-9256.2007.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Ballot Paper Photographs and Low-Information Elections in Ireland

Abstract: In an attempt to facilitate greater voting participation in the Republic of Ireland, photographs of candidates have been placed on the ballot paper for local, national and European elections. Limited research undertaken in advance of the implementation of the photograph policy advised that the measure would assist people with literacy problems. However, social psychology research has long demonstrated that people are willing to make considerable judgements about a person when shown a photograph. The advent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 14 publications
(15 reference statements)
0
30
0
Order By: Relevance
“…This judgement takes place immediately, and Willis and Todorov (2006) showed that the evaluation of a person is stable even if a picture was shown only for a very short period of time. Attractiveness matters for electoral success too, as experimental studies have shown where participants had to make a choice between different pictures (Antonakis and Dalgas 2009;Ballew and Todorov 2007;Little et al 2007;Sigelman et al 1987;Todorov et al 2005) and where physical attractiveness increased the likelihood of getting elected (Banducci et al 2008;Berggren et al 2010;Buckley et al 2007;King and Leigh 2009;Klein and Rosar 2005;Leigh and Susilo 2009;Rosar and Klein forthcomming;Rosar et al 2008;Sigelman et al 1987).…”
Section: Attractiveness and (Electoral) Successmentioning
confidence: 99%
See 1 more Smart Citation
“…This judgement takes place immediately, and Willis and Todorov (2006) showed that the evaluation of a person is stable even if a picture was shown only for a very short period of time. Attractiveness matters for electoral success too, as experimental studies have shown where participants had to make a choice between different pictures (Antonakis and Dalgas 2009;Ballew and Todorov 2007;Little et al 2007;Sigelman et al 1987;Todorov et al 2005) and where physical attractiveness increased the likelihood of getting elected (Banducci et al 2008;Berggren et al 2010;Buckley et al 2007;King and Leigh 2009;Klein and Rosar 2005;Leigh and Susilo 2009;Rosar and Klein forthcomming;Rosar et al 2008;Sigelman et al 1987).…”
Section: Attractiveness and (Electoral) Successmentioning
confidence: 99%
“…This attractiveness score is then used as an independent variable in statistical models estimating electoral success. Most such empirical studies on physical attractiveness focus on candidate choices in majoritarian elections such as direct candidate elections in Germany's mixed members system (Klein and Rosar 2005;Rosar et al 2008;Rosar and Klein forthcoming), Australia's national (King and Leigh 2009) and local level elections (Leigh and Susilo 2009) or the STV system in Ireland (Buckley et al 2007). In such elections, candidates matter a great deal.…”
Section: How To Study Effects Of Attractiveness?mentioning
confidence: 99%
“…Judgments of competence from briefly presented (i.e., 1/10 s) face images have predicted outcomes in elections for United States (US) congress [2], governor [3], and president [4]. Quick leadership judgments from faces have also been found to predict voting decisions in the United Kingdom [5], [6], Canada [7], Australia [8], Ireland [9], Italy [10], and Japan [11]. Children’s judgments of leadership can predict electoral success as well, and closely match leadership judgments made by adults [12].…”
Section: Introductionmentioning
confidence: 99%
“…Buckley et al (2007) base their analysis on a feature of local elections in the Republic of Ireland:…”
Section: Related Literaturementioning
confidence: 99%